Combined Scattering of Radiation Belt Electrons by Low‐Frequency Hiss: Cyclotron, Landau, and Bounce Resonances. Issue 5 (2nd March 2020) - Fu, Song; Yi, Juan; Ni, Binbin; Zhou, Ruoxian; Hu, Zejun; Cao, Xing; Gu, Xudong; Guo, Deyu
Abstract: Low‐frequency hiss is known to play an important role in the precipitation of radiation belt electrons by cyclotron, Landau, and bounce resonances. To investigate the potential combined scattering effect caused by these resonant processes, we analyze the resonant conditions and develop a full relativistic test particle code to quantify the net pitch angle scattering efficiency. It is indicated that the three resonance processes can coexist to scatter electrons at different energies and pitch angles, with the net pitch angle scattering rates up to 10 −3 s −1 for low‐frequency hiss 175 pT at L = 4.5. Comparisons with the quasi‐linear theory results demonstrate that the cyclotron resonance is mainly responsible for the pitch angle scattering of electrons < 80°, while both Landau and bounce resonances can affect the scattering of near‐equatorially mirroring electrons and their combined diffusion produces smaller scattering coefficients compared to quasi‐linear theory calculations. Plain Language Summary: The radiation belt electrons are believed to resonate with low‐frequency plasmaspheric hiss in ways of cyclotron, Landau, and bounce resonances. In previous quasi‐linear approximations, the wave‐particle interactions were separately evaluated through numerical calculations, where the cyclotron resonance is mainly responsible for pitch angle scattering of nonequatorially mirroring electrons with pitch angles <80°, and both Landau and bounce resonance are believed to effectively scatter near‐equatorially mirroring electrons. To examine the net scattering effect and determine the dominant scattering mechanism for near‐equatorially mirroring electrons, we simulate the electron scattering coefficients by test particle code and compare the results with quasi‐linear theory. Besides validating the contribution of low‐frequency hiss to radiation belt electron losses and the applicability of quasi‐linear theory, our investigation emphasizes the importance of combined scattering effect of cyclotron, Landau, and bounce resonances. Our results also suggest that the combined scattering cannot be treated by quasi‐linear formulism but should be incorporated into future simulations of radiation belt electron dynamics. Key Points: Cyclotron, Landau, and bounce resonances induced by low‐frequency hiss can coexist to scatter radiation belt electrons Test particle simulations validate the feasibility of quasi‐linear theory in that hiss‐induced pitch angle scattering of electrons < 80° is mainly predominated by cyclotron resonance Combined Landau and bounce resonances by low‐frequency hiss produce smaller pitch angle scattering coefficients for near‐equatorially mirroring electrons than previous quasi‐linear theory predictions